If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 76 + -5x = 5 + -7x Solving 76 + -5x = 5 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 76 + -5x + 7x = 5 + -7x + 7x Combine like terms: -5x + 7x = 2x 76 + 2x = 5 + -7x + 7x Combine like terms: -7x + 7x = 0 76 + 2x = 5 + 0 76 + 2x = 5 Add '-76' to each side of the equation. 76 + -76 + 2x = 5 + -76 Combine like terms: 76 + -76 = 0 0 + 2x = 5 + -76 2x = 5 + -76 Combine like terms: 5 + -76 = -71 2x = -71 Divide each side by '2'. x = -35.5 Simplifying x = -35.5
| 4(x-y)+4y-5x= | | x(1+3)=32 | | 3r-4(2r-5)=-15 | | 8-2(x+1)=-2(1-x) | | p+p+37+3p-40=922 | | 2(15G-15)+1/2(10G+12) | | 5-x=36 | | -(-3x-6x)=-32+5x | | x+(x*3)=32 | | p+p+37+3p-40=809 | | (x/(x-2))-(1/(x+1))=(1) | | (-3x-6x)=-32+5x | | xv+w=6 | | 19-10= | | 2.18=A/740 | | 6-(x-5)=-4 | | 18x-4y+(-8x)-2y= | | 1.5x+2.1=3 | | 8x-6=14+3x | | 5y-2x=-2 | | x+(x*3)=2 | | 50/9*9/50 | | 10a+4b= | | 7=-3(23-x)+2(x-2) | | ((-4x)/3)-(3/2)=((-5x)/4) | | 8x^2+39x+34=0 | | (3+4)(6+5x)=25-1.5(x+3) | | x+y-4=32 | | -16x-18=-15x | | 2(5x-1)=30 | | 14b-5b+4b= | | 13x^2+10x^2=23x^2 |